Brief Psychometric Statement on Addiction Diagnostics Questionnaire «ODA-2010» - A V Smirnov (Peoples' Friendship University of Russia (RUDN University), 2012)
The paper presents the results of developing and testing a new psychodiagnostic technique ODA-2010 intended for the diagnosis of addictive behaviors.